2019
DOI: 10.1007/s10450-019-00022-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of mesoporous polymeric microspheres of methacrylic derivatives of aromatic thiols

Abstract: The paper presents the synthesis and characterization of mesoporous microspheres of derivatives of three aromatic thiols: S-phenyl 2-methylprop-2-enethioate (PSM), S,S′-thiodi-4,1-phenylenebis(thiomethacrylate) (DMSPS), and bis[4(2-hydroxy-3-methacryloyloxypropoxy)phenyl]sulfide (BES.DM) with divinylbenzene (DVB). The microspheres were obtained by the emulsion-suspension polymerization procedure. The chemical and porous structure, morphology, and properties of the microspheres were analyzed by attenuated total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…For porous microparticles, it was observed that microparticles with the lowest DVB content (labeled as P 70 ) display a relatively low surface area of 148 m 2 /g, which increases to 552 m 2 /g, when the DVB content is increased to 100% (labeled as P 0 ). This can be attributed to the earlier phase separation of the polymer within the seed for the reaction mixture comprising a high DVB content, which is due to higher cross-linking density and consequently higher molecular weight. In addition, the same has been explained by Galia et al that the cross-linking agent is an important feature in the micropore formation within the particles . It was additionally reported that the higher surface area and increase in pore volume resulted as a consequence of increasing the DVB content in the particles, which results in an increase in the number of micropores.…”
Section: Results and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For porous microparticles, it was observed that microparticles with the lowest DVB content (labeled as P 70 ) display a relatively low surface area of 148 m 2 /g, which increases to 552 m 2 /g, when the DVB content is increased to 100% (labeled as P 0 ). This can be attributed to the earlier phase separation of the polymer within the seed for the reaction mixture comprising a high DVB content, which is due to higher cross-linking density and consequently higher molecular weight. In addition, the same has been explained by Galia et al that the cross-linking agent is an important feature in the micropore formation within the particles . It was additionally reported that the higher surface area and increase in pore volume resulted as a consequence of increasing the DVB content in the particles, which results in an increase in the number of micropores.…”
Section: Results and Discussionsupporting
confidence: 93%
“…It was additionally reported that the higher surface area and increase in pore volume resulted as a consequence of increasing the DVB content in the particles, which results in an increase in the number of micropores. The same trend observed in the present research has been evidenced and is reported in the literature. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Moreover, in the range of 900–650 cm −1 is possible to see deformation bands of C-H groups at benzene ring, therefore, the presence out of plane ring and H bending vibrations at 695 and 750 cm −1 is detected. Besides, the out of plane bending and twisted vibrations of vinyl groups at 908 and 991 cm −1 are observed [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The proposed organic-inorganic microspheres show promising properties, especially as adsorbents for the removal of heavy ions and organic compounds from aqueous solutions and selective materials for solid-phase extraction techniques, because of their well-developed porous structures. Also, these materials are characterized by good thermal resistance [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%